PENGEMBANGAN E-MODUL BARISAN DAN DERET BERBANTUAN LECTORA UNTUK MENGEKSPLOR KEMAMPUAN KONEKSI MATEMATIS SISWA SMK - Lisbadiyah, Ulpah; Ratnaningsih, Nani; Lestari, Puji (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2023)
The research produced an e-module of Lectora-assisted sequences and series to explore the mathematical connection abilities of Vocational High School students as well as to analyze and describe the quality of effectiveness of the mathematical connection abilities of Vocational High School students after using the Lectora-assisted sequence and series e-module. The method used in this study is the research and development method (Research & Development) with the ADDIE development model through the Analyze, Design, Develop, Implement and Evaluate stages to obtain a product that is valid and feasible to use. Based on the results of research and development, the researcher analyzes the stage conduct material and media needs analysis. At the design stage the researcher makes flowcharts and storyboards, designs test instruments, compiles validation sheets for material experts and media experts, creates user response questionnaires, the develop stage produces products that have been designed, conducts expert tests on material experts and media experts with validation results at category "very suitable for use", the implementation stage of the e-module is applied in learning activities to 27 students of class X Islamic Banking and the evaluate stage is known that the average value of students' mathematical connection abilities in the posttest is greater than the average value of students' mathematical connection abilities in pretest. The user response to the Lectora-assisted e-module is positive with the "very good" category. Effect Size (ES) test results obtained 1.45 "Strong Effect" category. Posttest results of students' mathematical connection abilities obtained as many as 66.7% of students with high criteria, 25.9% of students with medium criteria and 7.4% of students with low criteria. These results indicate that the Lectora-assisted sequence and series e-module in learning activities has a very good effect in exploring the mathematical connection abilities of SMK students.